Analisis Pengaruh Persepsi Harga Dan Lokasi Terhadap Keputusan Pembelian Konsumen Pada Steak Moen Moen Lampung - Natasha Lim; Roozana Maria Ritonga (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
This study aims to analyze the effect of Price Perception and Location on Consumer Purchase Decisions in Steak Moen Moen Lampung. This research was done with quantitative analysis through questionnaires. The population of this study was consumers of Steak Moen Moen Lampung who did a transaction at Steak Moen Moen Lampung in 2022. The sample in this study was 100 respondents using the purposive sampling technique. The data was analyzed using SPSS Vers 25. The results of the study stated that price perception and location have an influence of 41.5% on consumer purchase decisions. Based on the results of the T-test showed that price perception and location have a positive and significant effect on purchase decisions partially. The F-test results showed that price perception and location have a positive and significant effect on purchase decisions simultaneously. Based on the results of this study, suggestions for Steak Moen Moen Lampung are to maintain affordability, maintain competitive prices, keep the location accessible, and continue to update payment methods to keep up with the times.